Facile one-pot multi-component synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles via sp(3) C-H activation/functionalization of azaarenes - Pathan, Mohsinkhan Y.; Chavan, Santosh S.; Shaikh, Taufeekaslam M. Y.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Mulla, Shafeek A. R. (Chemistryselect, 2017)
A novel one-pot multicomponent reaction (MCR) protocol has been demonstrated for the first time for sustainable and facile synthesis of spirooxindoles and 3, 3 `-disubstituted oxindoles in an excellent yield via sp(3) C-H activation/functionalization of 2-methyl azaarenes and (2-azaaryl)methanes with isatin, active methylene compounds using eco-friendly heterogeneous, reusable silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst.
Keywords: 3; 3'-disubstituted oxindoles; azaarenes; silica-supported dodecatungstophosphoric acid (DTP/SiO2) catalyst; sp(3) C-H activation/functionalization; spirooxindoles